THE IMPLEMENTATION OF CONCRETE OBJECT MEDIA TO INCREASE ELEMENTARY STUDENTS’ LEARNING OUTCOMES ON FRACTION LEARNING MATERIAL - Hidayati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses how students in understanding fraction learning material can use concrete objects in the learning process. Hence, this paper describes the use of concrete object media on fraction learning material to enhance the student’s learning outcome. The research method used is Classroom Action Research through two cycles. The research subject was the third-grade students at SD Negeri X Palembang. The data were collected by using a test and observation sheet. The result reveals that the student’s learning outcomes increased to 40% from the pre-cycle (T0), 70% in cycle 1 (T1), and 90% in cycle 2 (T2). It means that concrete object media on fraction learning material could promote students’ learning outcomes